Universities, Stakeholders and Social Mission - Bogacz-Wojtanowska, Ewa; Jedynak, Piotr; Wrona, Sylwia; Pluszyńska, Anna (Taylor & Francis, 2022)
Today's universities are confronted with questions about the increasing scale of corporatisation and commercialisation, as well as their decreasing activity in the field of the social mission, i.e., engagement in the real problems of ordinary people, local communities and society at large. As a remedy for this problem, this book proposes using action research as a means of shaping collaboration between universities and their stakeholders, taking into account related benefits, opportunities and challenges. In this context, we understand action research somewhat more broadly, as universities’ conducting useful research that becomes a domain of their social mission. The core message of this volume is the development of a cooperation process in which the university leaves its ""ivory tower,"" builds relationships with its stakeholders and, as a result, engages more effectively in social life.